0026 Prehospital education for those treating motorcycle crash patients. (26th April 2015) - Irani, Tara; Meizoso, Jonathan; Garcia, George; Schulman, Carl; Lineen, Edward; Namias, Nicholas; Byers, Patricia
Abstract : Statement of purpose: In July 2000, Florida's universal helmet law was lessened to a partial helmet law despite unhelmeted riders being more likely to suffer serious and fatal head injuries. In response to these legislative changes and the increasing use of motorcycles among Floridians, we created an education program to teach early recognition of injuries with optimisation of care to prehospital personnel. This tertiary prevention program aims to mitigate the effect of motorcycle crash injuries by providing education focused on paramedic judgement for triage decisions, motorcycle injury patterns, and medical techniques, including fluid resuscitation, tourniquet use, helmet removal, cricothyroidotomy, and needle decompression. Methods/Approach: Prospective surveys given to 610 prehospital staff throughout the state of Florida from January 2012 to November 2013 were evaluated. Prehospital staff were generally male (80%) and had an average professional experience of 12 years. Biases toward motorcycle riders and pre-/post-test knowledge were evaluated. Subjects with previous motorcycle experience (n = 216) were compared to those with no motorcycle experience (n = 394). A Z-test for independent proportions was used where appropriate to compare test responses. Results: Subjects with previous motorcycle experience were significantly more likely to disagree or strongly disagree with the following statements when compared to those with no motorcycle experience: "Motorcycle crash victims are typically responsible for the crashes they get in" (60.4% vs. 45.1%; p < 0.001) and "Most traumas are the result of lack of ability, ignorance, laziness, or all three" (37.7% vs. 28.9%; p = 0.014). Conclusions: Our findings may suggest that individuals with previous motorcycle experience may be less likely to agree with the idea that motorcycle crash victims are typically responsible for the crashes they get in, and that most traumas are the result of lack of ability, ignorance, laziness, or all three of these factors. This difference in attitude may be worth evaluating further to determine whether there is a difference in approach to care. Significance and contribution to the field: We aim to highlight the purpose of this tertiary prevention program and the need for similar programs in other states without universal helmet laws. We will discuss particular management approaches unique to motorcyclists, the need for coordination and multidisciplinary care, triage and transport, and injuries commonly encountered in motorcyclists. We aim to improve the assessment, evaluation, transport time, and definitive management of the motorcycle crash patient, through education and by assessing potential biases of prehospital personnel. We hope to empower health care providers as stakeholders in the solution to take a more active role in prehospital education.